A clinical audit on the care of adult tuberculosis contacts in a public primary care clinic, Malaysia - Ching, Siew Mooi; Hassan, Faezah; Paimin, Fuziah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
The National Clinical Practice Guideline in Tuberculosis (TB) was designed to improve the quality of tuberculosis care. However, it remains unknown whether primary care doctors adhere to it well. This audit aims to assess the quality of care in the process of TB contact tracing in a primary care setting. Methods: Data on TB contact tracing from 1st February 2013 to 15th February 2013 was obtained retrospectively from all medical records of diagnosed pulmonary TB in a public primary care clinic. All patients who fulfilled the inclusion and exclusion criteria were included in the study. Results: A total of 102 medical records of adult TB contacts were recruited. The median age of the TB contact was 34 (IQR=10) years and 65 % were male. Seventy two percent of the adult TB contact had a TBIS 10C3 form created, and 95% of the medical records were fully documented. History taking and physical examination were recorded on 97% and 99% of patients respectively during the first follow-up at the polyclinic. Eighty five percent and 100% of the patients had a chest-x-ray and sputum direct smear for acid-fast bacilli done respectively. The turn-up rate for the first, second, third and fourth visit was 100% to 32%, 10% and 2% respectively. Conclusion: The quality of care for adult TB contacts tracing in this clinical audit was found to be suboptimal. There is a difference between the current national guidelines and practice in the clinic. Certain measures to improve the quality of care for adult TB contact tracing are urgently needed.